Driving model of land use change on the evolution of carbon stock: a case study of Chongqing, China - Luoshan Zheng; Yangbing Li; Yan Chen; Rong Wang; Shijie Yan; Chunhua Xia; Bing Zhang; Jing’an Shao (Environmental Science and Pollution Research, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Relative contribution of roots and symbiotic fungi to wheat nitrogen uptake and N2O emissions under straw burial - Zheng-Rong Kan; Yanling Li; Ruoyan Yang; Xinyu Yang; Qihang Wei; Ahmad Latif Virk; Jianying Qi; Feng-Min Li; Zichang Zhang; Haishui Yang (Rhizosphere, 2023)

Oligo (ethylene glycol) side chain engineering: An efficient way for boosting the development of green-solvent processable electrochromic devices - Shiyi Li; Qilin Wang; Yuehui Zhai; Zhen Xing; Jundong Zhong; Danming Chao; Xuanbo Zhu; Changru Rong; Zongquan Wu; Zheng Chen (Chemical Engineering Journal, 2023)

Effects of Different Conditioners on Humus Composition and Humic Acid Structural Characteristics in Black Soil Under the Combined Application of Pig Manure and Straw - Shuang Zheng; Jing-Gui Wu; Jin-Rong Li; Juan Hu; Li He (Journal of Soil Science and Plant Nutrition, 2023)

Impacts of interprovincial migration on the household energy footprints in China - Rong Yuan; Nan Li; Shenglin Zheng (Applied Geography, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Climatic aridification restrained late Cenozoic denudation of the Tian Shan in the inland of Asia - Yutong Jiang; Honghua Lu; Ruohong Jiao; Lichen Pang; Rong Yang; Menghan Wu; Xiangmin Zheng; Youli Li (Global and Planetary Change, 2023)

Quantum chemical calculation assisted efficient lithium extraction from unconventional oil and gas field brine by β-diketone synergic system - Yunze Zhao; Huifang Xing; Meng Rong; Zheng Li; Xuetuan Wei; Congmei Chen; Huizhou Liu; Liangrong Yang (Desalination, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

Detecting endosperm cracks in soaked maize using μCT technology and R-YOLOv7-tiny - Yitao Jiao; Zheng Wang; Yuying Shang; Rong Li; Zhixin Hua; Huaibo Song (Computers and Electronics in Agriculture, 2023)

The impact of crop residue return on the food–carbon–water–energy nexus in a rice–wheat rotation system under climate warming - Li-Yao Zhou; Yong-he Zhu; Zheng-Rong Kan; Feng-Min Li; Feng Zhang (Science of The Total Environment, 2023)

Soil microbial community compositions and metabolite profiles of Achnatherum inebrians affect phytoremediation potential in Cd contaminated soil - Jie Jin; Chao Wang; Ronggui Liu; Jiyi Gong; Jianfeng Wang; Xueli Niu; Rong Zheng; Zhonglong Tang; Kamran Malik; ChunJie Li (Journal of Hazardous Materials, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Alignment of Fe3O4/CNT electrodes via magnetic blade printing for wireless stress-direction-recognizing strain sensor - Guangwei Wang; Chenhao Cong; Xianbing Zheng; Hongjiang Li; Fuhao Jiang; Xuhao Wang; Rong Li; Mingliang Jin; Pengfei Zhang; Junru Li; Chuanwei Zhang; SeHyun Kim; et al. (Chemical Engineering Journal, 2023)

Forest degradation caused by dwarf bamboo overabundance reduces soil C, N and P stocks in giant panda habitat - Li Mo; Hao Yang; Rong Hou; Wei Wu; Xinqiang Song; Hong Yang; Zhisong Yang; Weichao Zheng; Dunwu Qi (CATENA, 2023)

Effect of 5-Aminolevulinic Acid Photodynamic Therapy on Aspergillus fumigatus Biofilms in Vitro - Zhimin Duan; Jianbo Tong; Nana Zheng; Rong Zeng; Yuzhen Liu; Min Li (Current Microbiology, 2023)
Aspergillus fumigatus biofilm development results in enhanced pathogenicity and treatment resistance. Most contemporary antibiotics, however, are unable to eliminate biofilms. In recent years, with the application of new photosensitizers and the development of treatment, ALA-PDT (5-aminolevulinic acid photodynamic treatment) has achieved remarkable curative effect in the treatment of fungal infectious diseases; however, no research has been conducted on ALA-PDT against A. fumigatus . This study investigated the inhibitory effect of ALA-PDT at various 5-aminolevulinic acid concentrations and light doses on A. fumigatus planktonic and biofilms in vitro. We found that ALA-PDT may successfully inhibit the development of A. fumigatus biofilm and disintegrate mature biofilm. After ALA-PDT treatment, the adherence rate and vitality dramatically decreased, and the biofilm’s structure was severely compromised. Our findings show for the first time that ALA-PDT may be used to prevent the formation of A. fumigatus biofilm and disturb the structure of mature biofilm, and that it could be employed as a therapeutic therapy for A. fumigatus superficial infection.

Characterization of elastoplastic behavior and retrieval of active zone depth for expansive soil slopes in the middle-route channel head of the South-to-North Water Diversion Project, China, using InSAR time series - Ziyuan Li; Jun Hu; Xing Zhang; Wanji Zheng; Wenqing Wu; Yaogang Chen; Pinjun Tang; Rong Gui (Remote Sensing of Environment, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Arbuscular mycorrhizal fungi mitigate earthworm-induced N2O emissions from upland soil in a rice-rotated wheat farming system - Zheng-Rong Kan; Qihang Wei; Ruoyan Yang; Yanling Li; Jiajia Zhou; Jianying Qi; Feng-Min Li; Haishui Yang (Applied Soil Ecology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Impacts of targeted poverty alleviation on urban-rural residential energy consumption inequality: Evidence from 178 Chinese prefecture-level cities - Nan Li; Rong Yuan; Shenglin Zheng (Urban Climate, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Removal of iodide anions in water by silver nanoparticles supported on polystyrene anion exchanger - Li Li; Su-Juan Yu; Rong-Gang Zheng; Peng Li; Qing-Cun Li; Jing-Fu Liu (Journal of Environmental Sciences, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

Secukinumab plays a synergistic role with starvation therapy in promoting autophagic cell death of hepatocellular carcinoma via inhibiting IL-17A-increased BCL2 level - Rong Tang; Linmei Zheng; Jinfang Zheng; Jincai Wu; Pingping Chen; Jiacheng Chen; Dafeng Xu; Yongchao Zeng; Qijin Li; Zhensheng Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Biochar enhanced organic matter transformation during pig manure composting: Roles of the cellulase activity and fungal community - Yanan Yin; Mengtong Li; Xiaohui Tao; Chao Yang; Wenrong Zhang; Haichao Li; Yucong Zheng; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Degradation of polymeric polyproanthocyanidins from black chokeberry by microwave-assisted nucleophilic technique of sulfite/catechin: Reaction kinetics, antioxidation and structural analysis - Miao Li; Pu Li; Yufeng Xu; Baiqing Zhang; Jinfeng Li; Weitian Zhong; Hui Zang; Hui Zheng; Haifeng Rong; Fengming Ma (Food Chemistry, 2023)

Air-water interfacial properties and quantitative description of pea protein isolate-Tween 20 - Qian Shen; Wei Zheng; Fei Han; Jingnan Zuo; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Considering flood scaling property in multi-objective calibration of the SWAT model: a case study in Zijinguan watershed, Northern China - Yanchen Zheng; Jianzhu Li; Ting Zhang; Youtong Rong; Ping Feng (Natural Hazards, 2023)

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Methane emission under straw return is mitigated by tillage types depending on crop growth stages in a wheat-rotated rice farming system - Zheng-Rong Kan; Yifan Li; Xinyu Yang; Silong Zhai; Yi Meng; Chaofan Xu; Jianying Qi; Feng-Min Li; Changqing Chen; Haishui Yang (Soil and Tillage Research, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Genome-wide DNA methylation and transcription analysis reveal the potential epigenetic mechanism of heat stress response in the sea cucumber Apostichopus japonicus - Mengyang Chang; Jianlong Ge; Meijie Liao; Xiaojun Rong; Yingeng Wang; Bin Li; Xinrong Li; Jinjin Wang; Zheng Zhang; Yongxiang Yu; Chunyuan Wang (Frontiers in Marine Science, 2023)
DNA methylation is an important epigenetic modification that regulates many biological processes. The sea cucumber Apostichopus japonicus often suffers from heat stress that affects its growth and leads to significant economic losses. In this study, the mRNA expression patterns and DNA methylation characteristics in the body wall of A. japonicus under heat stress were analyzed by whole-genome bisulfite sequencing (WGBS) and transcriptome sequencing (RNA-seq). We found that CpG was the main DNA methylation type, and heat stress caused a significant increase in the overall methylation level and methylation rate, especially in the intergenic region of the A. japonicus genome. In total, 1,409 differentially expressed genes (DEGs) and 17,927 differentially methylated genes (DMGs) were obtained by RNA-seq and WGBS, respectively. Association analysis between DNA methylation and transcription identified 569 negatively correlated genes in both DMGs and DEGs, which indicated that DNA methylation affects on transcriptional regulation in response to heat stress. These negatively correlated genes were significantly enriched in pathways related to energy metabolism and immunoregulation, such as the thyroid hormone signaling pathway, renin secretion, notch signaling pathway and microRNAs in cancer. In addition, potential key genes, including heat shock protein ( hsp70 ), calcium-activated chloride channel regulator 1( clca1 ), and tenascin R ( tnr ), were obtained and their expression and methylation were preliminarily verified. The results provide a new perspective for epigenetic and transcriptomic studies of A. japonicus response to heat stress, and provide a reference for breeding sea cucumbers resistant to high temperatures.

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

ShuffleNet-Triplet: A lightweight RE-identification network for dairy cows in natural scenes - Yunfei Wang; Xingshi Xu; Zheng Wang; Rong Li; Zhixin Hua; Huaibo Song (Computers and Electronics in Agriculture, 2023)

E3D: An efficient 3D CNN for the recognition of dairy cow's basic motion behavior - Yunfei Wang; Rong Li; Zheng Wang; Zhixin Hua; Yitao Jiao; Yuanchao Duan; Huaibo Song (Computers and Electronics in Agriculture, 2023)

Straw incorporation interacting with earthworms mitigates N2O emissions from upland soil in a rice-wheat rotation system - Zheng-Rong Kan; Jiajia Zhou; Feng-Min Li; Mohamed S. Sheteiwy; Jianying Qi; Changqing Chen; Haishui Yang (Science of The Total Environment, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Ex vivo coronary endothelial cell activation associated with indoor coal combustion initiated atherosclerosis - Wanjun Zhang; Yaxian Pang; Wenting Cheng; Tao Wang; Yanting Li; Xin Li; Jianzhong Zhang; Xiaowen Xia; Yuxin Zheng; Rong Zhang; Jinglong Tang (Science of The Total Environment, 2023)

Biochar reduces bioavailability of phosphorus during swine manure composting: Roles of phoD-harboring bacterial community - Yanan Yin; Chao Yang; Mengtong Li; Sai Yang; Xiaohui Tao; Yucong Zheng; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2023)

Soil organic carbon regulates CH4 production through methanogenic evenness and available phosphorus under different straw managements - Zheng-Rong Kan; Zirui Wang; Wei Chen; Ahmad Latif Virk; Feng-Min Li; Jian Liu; Yaguang Xue; Haishui Yang (Journal of Environmental Management, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

An in silico and in vitro integrated analysis method to reveal the curative mechanisms and pharmacodynamic substances of Bufei granule on chronic obstructive pulmonary disease - Yuan-yuan Ma; Rong Li; Zhi-xian Shang; Wei Liu; Xin-yi Jiao; Liu-yi Liang; Rui Liu; Zheng Li (Molecular Diversity, 2023)

Enhanced phytoremediation of atrazine-contaminated soil by vetiver (Chrysopogon zizanioides L.) and associated bacteria - Faming Zhang; Shixian Sun; Yuhong Rong; Lili Mao; Shuchun Yang; Ling Qian; Rongbiao Li; Yi Zheng (Environmental Science and Pollution Research, 2023)

Degradation of antibiotics by electrochemical advanced oxidation processes (EAOPs): Performance, mechanisms, and perspectives - Qingbin Yuan; Siyao Qu; Rong Li; Zheng-Yang Huo; Yan Gao; Yi Luo (Science of The Total Environment, 2023)

Trends in drought and effects on carbon sequestration over the Chinese mainland - Yang Li; Mengdi Li; Zhicheng Zheng; Wei Shen; Yanan Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Strengthen the purification of eutrophic water and improve the characteristics of sediment by functional ecological floating bed suspended calcium peroxide and sponge iron jointly - Zheng Zhu; Yi Wang; Xue-Yi Han; Wen-Huai Wang; Hao-Min Li; Zi-Qi Yue; Wei Chen; Fu-Rong Xue (Journal of Environmental Management, 2023)

Application of group method of data handling and gene expression programming for predicting solubility of CO2-N2 gas mixture in brine - Qichao Lv; Tongke Zhou; Rong Zheng; Reza Nakhaei-Kohani; Masoud Riazi; Abdolhossein Hemmati-Sarapardeh; Junjian Li; Weibo Wang (Fuel, 2023)

Trade-offs between poverty alleviation and household energy intensity in China - Nan Li; Rong Yuan; Shenglin Zheng (Environmental Impact Assessment Review, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

The key role of carboxylate ligands in Ru@Ni-MOFs/NF in promoting water dissociation kinetics for effective hydrogen evolution in alkaline media - Cheng-Fei Li; Ting-Yu Shuai; Li-Rong Zheng; Hai-Bo Tang; Jia-Wei Zhao; Gao-Ren Li (Chemical Engineering Journal, 2023)